IMPROVEMENT OF BAND-WIDTH PERFORMANCE OF HAIPRPIN BAND-PASS FILTER USING DEFECTED GROUND STRUCTURES - A. Zakriti; N. Amar Touhami; K. Bargach; M. Lamsalli; M. Essaidi (European Scientific Journal, ESJ, 2013)
In this paper, a novel technique for improving the return loss of three poles hairpin band-pass filter incorporating defected ground structure is presented. As a result, the structure is simple, wideband with compact size. The expected result of a BPF with DGS is to have a compact band-pass filter with significantly improvement in return loss. The filter performances are exhibits |S21| more than -0.5 dB, |S11| less than -30dB, and center frequency of proposed filter is around 4.2GHz with operating bandwidth of 35%.